Evaluating the role of post-harvest glyphosate application in enhancing weed control in winter wheat - Serim,Ahmet Tansel; Asav,Ünal; Kaya,Yalçın; Başaran,Bülent; Patterson,Eric L. (PeerJ, 2025)
Changes in the timing and intensity of spring rainfall have led to a significant increase in late-season weed emergence in Türkiye. These newly emerged weeds tend to grow more vigorously due to the absence of competition with crops and other weeds during their development. Two field experiments were conducted in continuous monoculture winter wheat over three growing seasons (2020–2023) in Türkiye. The first goal was to determine the impact of post-harvest herbicide (PHH) on the critical time for weed removal (CTWR) in winter wheat, and the second goal was to evaluate the effects of PHH combined with various weed control treatments on weed populations, the soil seed bank, and crop yield. The experiment followed a split-plot design, with the PHH regimes and weed removal timing or weed control treatments serving as the main and sub-plots, respectively. The herbicide regime included post-harvest glyphosate potassium salt (PHG) applied at 2.646 kg ai ha−1 and No PHG. Weed removal timings were set at 10-day intervals, from 0 to 110 days after wheat emergence (DAE). Weedy and weed-free controls were included for comparison. The weed control treatments involved post-emergence tribenuron-methyl at 7.5 g ai ha−1 and hand weeding. The application of the PHG delayed the CTWR from 416 growing degree days (GDD) to 516.5 GDD in 2022 and from 465.6 GDD to 661.2 GDD in 2023, effectively preventing yield loss. The combined use of PHG with post-emergence tribenuron-methyl or hand weeding maximized wheat yield while minimizing the weed flora and the size of the soil seed bank.
Keywords: Winter wheat; Post-harvest herbicide; Soil seed bank; Glyphosate potassium salt; Tribenuron-methyl; Growing degree days; Critical time for weed removal